A copper alloy double-headed stud for guiding new energy DC motor and its cold heading forming process

By adding trace elements and nanoparticles to aluminum bronze matrix materials, and adopting two-step heat treatment and segmented multi-step cold heading forming process, the strength, durability and forming accuracy of double-headed studs in new energy DC motors are solved. The problem has significantly improved the overall performance of the stud.

CN119187420BActive Publication Date: 2025-02-18ZHEJIANG KESHUO FASTENER CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411719353.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-28
Publication Date
2025-02-18
Estimated Expiration
2044-11-28

AI Technical Summary

Technical Problem

In new energy DC motors, existing double-headed studs are difficult to meet the requirements of high strength, durability and forming accuracy due to high stress and frequent temperature changes. In traditional cold heading forming processes, they have limitations on material forming accuracy and surface quality. sex.

Method used

By adding trace elements such as yttrium, lanthanum, magnesium, titanium, zirconium, boron to the aluminum bronze matrix material, and adding nanotungsten carbide and nanoalumina particles, combining two-step heat treatment and segmented multi-step cold heading forming process, it is significant The wear resistance, fatigue resistance and forming accuracy of the stud are improved.

Benefits of technology

It significantly improves the strength, ductility, wear resistance, dimensional stability and fatigue resistance of the double-headed studs, meets the demand for high-performance double-headed studs of new energy DC motors, extends the service life and improves the finished product rate. .

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The present invention relates to a cold heading forming process for a stud, and in particular to a copper alloy stud for a new energy DC motor guide and a cold heading forming process thereof. The present invention significantly improves the wear resistance, fatigue resistance and forming accuracy of the stud by adding trace elements such as yttrium, lanthanum, magnesium, titanium, zirconium, boron, etc. to an aluminum bronze matrix material, and by adding nano-tungsten carbide and nano-alumina particles, combined with double-step heat treatment and segmented multi-step cold heading forming, thereby meeting the high performance requirements of new energy DC motors for studs.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a double-headed stud cold heading forming process, and in particular to a copper alloy double-headed stud guided by a new energy direct current motor and a cold heading forming process thereof. Background Art

[0002] With the development of new energy technologies, DC motors are increasingly used in new energy vehicles, wind power generation and other fields, and the performance requirements for their key components are also increasing. As one of the guide parts of the DC motor, the stud bolt is responsible for fixing and connecting the internal components of the motor. Its performance has an important impact on the reliability and stability of the overall operation of the motor. However, since DC motors need to withstand high mechanical stress and frequent temperature changes during operation, the guide stud bolt must have excellent strength, wear resistance, conductivity and fatigue resistance to ensure long-term stable operation in harsh working environments.

[0003] Existing studs are usually made of traditional aluminum bronze (CuAl 10 Fe3Mn2), although it has certain conductivity and corrosion resistance, the ductility and fatigue resistance of traditional copper alloys are relatively low under high stress, high-frequency impact and temperature change conditions, making it difficult to fully meet the requirements of new energy DC motors for high strength, durability and forming accuracy. In addition, the existing stud manufacturing process mainly relies on traditional machining and cold heading methods, which have certain limitations in material forming accuracy and surface quality, and are prone to cracks, stress concentration and other problems, affecting the reliability and service life of the finished product.

[0004] In order to solve the above problems, the industry has gradually introduced copper alloy materials reinforced with trace elements and nanoparticles to improve the mechanical strength, ductility and fatigue resistance of studs; and adopted more sophisticated forming control processes, such as segmented multi-step cold heading and local heating, to improve cold heading accuracy and material ductility. However, how to reasonably add trace elements and nanoparticles to copper alloys and optimize heat treatment and cold heading processes is still a technical problem in this field, and an innovative cold heading process is urgently needed to further improve the performance of studs. Summary of the invention

[0005] In view of the deficiencies in the prior art, the present invention proposes a cold heading forming process for a copper alloy stud for guiding a new energy DC motor. By adding trace elements such as yttrium, lanthanum, magnesium, titanium, zirconium, and boron to an aluminum bronze matrix material, and combining the addition of nano-tungsten carbide and nano-aluminum oxide particles, and combining double-step heat treatment and segmented multi-step cold heading forming, the wear resistance, fatigue resistance and forming accuracy of the stud are significantly improved, thereby meeting the high performance requirements of new energy DC motors for studs.

[0006] In order to achieve the above-mentioned purpose, the present invention adopts the following technical solutions:

[0007] A cold heading forming process for a copper alloy stud for guiding a new energy DC motor, characterized in that the process comprises the following steps:

[0008] 1) Material pretreatment: Choose aluminum bronze CuAl 10 Fe3Mn2 is used as a matrix material, and trace elements of yttrium, lanthanum, magnesium, titanium, zirconium and boron are added to the matrix material, and the contents of the trace elements are: yttrium and lanthanum are 0.01-0.15%, magnesium is 0.2-0.5%, titanium and zirconium are 0.01-0.05%, and boron is 0.01-0.03%; and nano-tungsten carbide and nano-alumina particles are added to the material, and the addition amount of the nano-particles is 0.01-0.1%;

[0009] 2) Two-step heat treatment: The modified copper alloy is heated to 700-750℃ and kept at this temperature for 1-2 hours, followed by rapid cooling to obtain a material with refined grains; then low-temperature tempering is performed at 250-300℃ for 1-2 hours to evenly distribute trace elements, eliminate internal stress, and improve material ductility and fatigue resistance;

[0010] 3) Segmented multi-step cold heading: The material is subjected to segmented multi-step forming on the cold heading machine.

[0011] Preferably, the amount of yttrium added is 0.005%-0.1%, and the amount of lanthanum added is 0.005%-0.1%.

[0012] Preferably, the added amount of titanium is 0.005-0.04%, and the added amount of zirconium is 0.005-0.03%.

[0013] Preferably, the addition amount of the nano-tungsten carbide is 0.005-0.08% and the addition amount of the nano-alumina particles is 0.005-0.05%.

[0014] Preferably, the segmented multi-step cold heading forming step includes the following sub-steps:

[0015] a) Preforming: Use a cold heading machine to preliminarily shape the copper alloy billet to obtain the basic shape of the stud;

[0016] b) Local heating fine forming: The thread and end structure of the stud are heated by induction heating to increase the local temperature to 200-250℃ to increase ductility and improve forming accuracy;

[0017] c) Final forming: Further fine forming is performed to obtain the final stud structure to ensure its dimensional accuracy and strength.

[0018] Preferably, the heating temperature in the local heating fine forming step is 200-250° C., and the heating time is 1-2 seconds.

[0019] Preferably, the punching pressure in the preforming stage of the segmented multi-step cold heading forming step is 15-20 tons, the punching pressure in the fine forming stage is 20-25 tons, and the punching pressure in the final forming stage is 25-30 tons.

[0020] Preferably, the surface of the mold used in the segmented multi-step cold heading step has a nano-composite coating, and the coating is a TiN / CrN nano-multilayer composite coating or a boron nitride (BN) self-lubricating coating.

[0021] Preferably, after the cold heading, the stud is rapidly isothermally cooled to room temperature.

[0022] Furthermore, the present invention also discloses a copper alloy double-headed stud obtained by the cold heading forming process.

[0023] The present invention adopts the above-mentioned technical solution, and significantly improves the comprehensive performance of the copper alloy stud for new energy DC motor guide through technical means such as material modification, two-step heat treatment and segmented multi-step cold heading. The specific technical effects are as follows:

[0024] 1. Improve material strength and ductility: By adding trace elements such as yttrium, lanthanum, magnesium, titanium, zirconium and boron to the aluminum bronze matrix, and introducing nano-tungsten carbide and nano-aluminum oxide particles, the alloy grain structure is effectively refined and the matrix material is strengthened. These added elements and nanoparticles are distributed in the copper alloy, which can hinder dislocation movement and grain boundary sliding, significantly enhance the strength and ductility of the material, and enable the stud to still have good deformation resistance under high stress environment.

[0025] 2. Improve wear resistance and fatigue resistance: Trace elements such as titanium and zirconium work synergistically with nano-tungsten carbide and nano-alumina particles, which not only improve the hardness and wear resistance of the material surface, but also effectively reduce the probability of micro-cracks in the material during cold heading, thereby improving the fatigue resistance of the stud under multiple cyclic stress and extending its service life.

[0026] 3. Optimize internal stress and dimensional stability: The two-step heat treatment process further optimizes the internal microstructure of the material through a combination of high-temperature heating, rapid cooling and low-temperature tempering, evenly distributes trace elements, and eliminates residual internal stress generated during cold heading. The final stud has higher dimensional stability and can withstand temperature and stress changes for a long time without deformation, which improves the reliability of the stud.

[0027] 4. Improve forming accuracy and yield rate: The segmented multi-step cold heading forming combined with local heating technology can significantly improve the dimensional accuracy and surface quality of the stud by finely controlling the temperature, pressure and forming steps when forming the key structures of the stud (such as threads and ends). This process reduces cracks or deformation caused by stress concentration or processing errors in the traditional cold heading process and improves the yield rate.

[0028] 5. Extend the life of the mold: The present invention adopts a nano-composite coating mold in the cold heading process. The TiN / CrN nano-multilayer coating or boron nitride (BN) self-lubricating coating on the mold surface reduces the friction coefficient and reduces the friction and wear between the mold and the copper alloy material, which not only improves the service life of the mold, but also ensures the stability and precision of cold heading. DETAILED DESCRIPTION

[0029] The following is a clear and complete description of the technical solutions in the embodiments of the present invention in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0030] The present invention provides a cold heading forming process for a copper alloy double-headed stud for guiding a new energy DC motor. The strength, ductility, wear resistance, dimensional stability and fatigue resistance of the stud are significantly improved through a combination of material modification, double-step heat treatment and segmented multi-step cold heading forming process. The following are the specific implementation steps of the process.

[0031] 1. Process steps

[0032] 1) Material pretreatment:

[0033] Choose Aluminum Bronze CuAl 10 Fe3Mn2 is used as the matrix material, to which trace elements of yttrium, lanthanum, magnesium, titanium, zirconium and boron are added, with the contents being 0.01-0.15% for yttrium and lanthanum, 0.2-0.5% for magnesium, 0.01-0.05% for titanium and zirconium, and 0.01-0.03% for boron.

[0034] Nano-tungsten carbide (WC) and nano-aluminum oxide (Al2O3) particles are evenly distributed in the matrix material, with an addition amount of 0.01-0.1%, to improve the strength, wear resistance and ductility of the matrix.

[0035] 2) Two-step heat treatment:

[0036] The first step is to heat the modified copper alloy to 700-750℃ and keep it for 1-2 hours, and then quickly cool it to room temperature to refine the grains and improve the strength and toughness of the material.

[0037] Step 2: Low temperature tempering at 250-300℃ for 1-2 hours to evenly distribute the trace elements in the material, eliminate internal stress and improve the ductility and fatigue resistance of the material.

[0038] 3) Segmented multi-step cold heading:

[0039] Use a multi-station cold heading machine to perform segmented multi-step forming on heat-treated materials.

[0040] Step a: Pre-forming, the punching force is 15-20 tons; the blank is preliminarily formed to form the basic structural outline of the stud.

[0041] Step b: local heating and fine forming, with a punching force of 20-25 tons; the local temperature of the thread and end structure of the stud is raised to 200-250°C by induction heating to enhance the ductility of the material and improve the forming accuracy.

[0042] Step c: Final forming, with a punching force of 25-30 tons; further forming to obtain the final stud structure to ensure its dimensional accuracy and strength.

[0043] 4) Rapid isothermal cooling: After cold heading, the stud is rapidly isothermally cooled to room temperature to maintain a uniform cooling rate, eliminate residual stress, and improve the dimensional stability of the stud.

[0044] Example 1

[0045] Material ratio: 0.1% yttrium, 0.1% lanthanum, 0.3% magnesium, 0.03% titanium, 0.02% zirconium and 0.02% boron are added to aluminum bronze; the contents of nano-tungsten carbide and nano-alumina particles are 0.05% and 0.03% respectively.

[0046] Heat treatment: The first step is heating to 720℃, keeping warm for 1.5 hours, and cooling rapidly; the second step is tempering at 270℃ for 1.5 hours.

[0047] Cold heading: segmented multi-step cold heading, local heating temperature is 220℃, heating time is 2 seconds.

[0048] Example 2

[0049] Material ratio: 0.08% yttrium, 0.08% lanthanum, 0.4% magnesium, 0.025% titanium, 0.015% zirconium and 0.02% boron are added to aluminum bronze; the contents of nano-tungsten carbide and nano-alumina particles are 0.04% and 0.025% respectively.

[0050] Heat treatment: The first step is heating to 740℃, keeping warm for 1 hour, and cooling rapidly; the second step is tempering at 260℃ for 1 hour.

[0051] Cold heading: segmented multi-step cold heading, local heating temperature is 230℃, heating time is 1.5 seconds.

[0052] Example 3

[0053] Material ratio: 0.12% yttrium, 0.12% lanthanum, 0.5% magnesium, 0.04% titanium, 0.03% zirconium and 0.025% boron are added to aluminum bronze; the contents of nano-tungsten carbide and nano-alumina particles are 0.06% and 0.04% respectively.

[0054] Heat treatment: The first step is heating to 750℃, keeping warm for 1.5 hours, and rapid cooling; the second step is tempering at 280℃ for 1 hour.

[0055] Cold heading: segmented multi-step cold heading, local heating temperature is 250℃, heating time is 1 second.

[0056] Comparative Example 1

[0057] Material ratio: No trace elements and nanoparticles are added to the aluminum bronze. Other technical features are the same as those in Example 1.

[0058] Comparative Example 2

[0059] Material ratio: 0.1% yttrium and 0.1% lanthanum are added to aluminum bronze, but no trace elements of magnesium, titanium, zirconium, boron, or nanoparticles are added. Other technical features are the same as those in Example 1.

[0060] Comparative Example 3

[0061] Material ratio: 0.08% yttrium, 0.08% lanthanum and 0.3% magnesium are added to aluminum bronze, but titanium, zirconium and boron are not added, and the contents of nano-tungsten carbide and nano-aluminum oxide particles are 0.03% and 0.02% respectively. Other technical features are the same as in Example 1.

[0062] Comparative Example 4

[0063] Material ratio: 0.1% yttrium, 0.1% lanthanum, 0.3% magnesium, 0.03% titanium, 0.02% zirconium and 0.02% boron are added to aluminum bronze; the contents of nano-tungsten carbide and nano-alumina particles are 0.05% and 0.03% respectively.

[0064] No heat treatment is performed.

[0065] Other technical features are the same as those in Example 1.

[0066] Comparative Example 5

[0067] Material ratio: 0.1% yttrium, 0.1% lanthanum, 0.3% magnesium, 0.03% titanium, 0.02% zirconium and 0.02% boron are added to aluminum bronze; the contents of nano-tungsten carbide and nano-alumina particles are 0.05% and 0.03% respectively.

[0068] Heat treatment: The first step is heating to 720℃, keeping warm for 1.5 hours, and rapid cooling; there is no second step of low-temperature tempering treatment.

[0069] Other technical features are the same as those in Example 1.

[0070] Test example

[0071] In order to verify the technical effects of the materials of the embodiments and comparative examples in terms of strength, ductility, wear resistance, dimensional stability and fatigue resistance, systematic experimental tests were conducted on the samples of embodiments 1, 2, 3 and comparative examples 1-5. The specific test methods and data are as follows:

[0072] 1. Experimental Methods

[0073] Material strength and ductility testing:

[0074] The tensile test was carried out using an electronic universal testing machine to test the sample and measure the tensile strength and elongation of the material.

[0075] Tensile test standard: According to GB / T 228.1 standard.

[0076] Results recorded: tensile strength (MPa) and elongation (%).

[0077] Wear resistance test:

[0078] The wear resistance test was carried out using a wear tester. The samples were subjected to friction and wear tests at the same friction load and rotation speed, and the wear amount was measured.

[0079] Abrasion resistance test standard: in accordance with GB / T 12444 standard.

[0080] Result record: wear amount (mg).

[0081] Internal stress and dimensional stability tests:

[0082] The residual stress of the material is detected by X-ray stress tester, and the dimensional change of the stud after cold heading is measured.

[0083] Dimensional stability test standard: According to GB / T 5319 standard.

[0084] Results recorded: residual stress (MPa) and dimensional deviation after forming (mm).

[0085] Anti-fatigue performance test:

[0086] The samples were fatigue tested using a high-frequency fatigue testing machine to record the fatigue life (number of cycles) of the material under specific cyclic stress.

[0087] Anti-fatigue test standard: According to GB / T 3075 standard.

[0088] Result record: Fatigue life (number of cycles).

[0089] 2. Experimental Results

[0090] The following table records the test data of Examples 1-3 and Comparative Examples 1-5.

[0091] Sample No. Tensile strength(MPa) Elongation(%) Wear amount (mg) Residual stress (MPa) Dimensional deviation(mm) Fatigue life (number of cycles) Example 1 616 21.5 18 120 0.02 1,800,000 Example 2 622 22.4 17 115 0.018 1,850,000 Example 3 633 23.5 16 112 0.015 1,900,000 Comparative Example 1 542 15.2 28 185 0.05 950,000 Comparative Example 2 563 16.8 26 172 0.045 1,000,000 Comparative Example 3 570 17.4 24 165 0.04 1,100,000 Comparative Example 4 603 18.6 22 158 0.035 1,200,000 Comparative Example 5 605 19.4 20 144 0.03 1,300,000

[0092] 3. Experimental Results Analysis

[0093] 1. Material strength and ductility:

[0094] Examples 1-3 are superior to the comparative example samples in terms of tensile strength and elongation, especially Example 3, whose tensile strength reaches 630 MPa and elongation is 23%. This shows that the strength and ductility of the material are significantly improved by the composite addition of trace elements and nanoparticles and the optimized two-step heat treatment.

[0095] Comparative Example 1 did not undergo material modification, and the tensile strength and elongation were significantly lower. Comparative Examples 2 and 3 only partially added trace elements, and the material strength and elongation were slightly improved, but not as good as the embodiment.

[0096] 2. Wear resistance:

[0097] The wear amount of Examples 1-3 is relatively small, especially the wear amount of Example 3 is 16 mg, which is better than the comparative sample and shows good wear resistance. The addition of nano-tungsten carbide and nano-aluminum oxide particles has a significant effect on improving wear resistance.

[0098] Comparative Example 1 has no material modification and has a higher wear amount (28 mg); after partial modification of Comparative Examples 2 and 3, the wear amount is reduced, but still higher than that of the embodiment.

[0099] 3. Internal stress and dimensional stability:

[0100] The residual stress of Examples 1-3 is significantly lower than that of the comparative example, especially the residual stress of Example 3 is reduced to 110 MPa, and the dimensional deviation is only 0.015 mm. This shows that the double-step heat treatment can effectively eliminate the residual stress inside the material and ensure dimensional stability.

[0101] Comparative Examples 4 and 5 did not undergo a complete two-step heat treatment, and the residual stress was relatively high and the dimensional deviation was also relatively large, indicating that the lack of low-temperature tempering or two-step heat treatment affected the stability of the material.

[0102] 4. Anti-fatigue performance:

[0103] Examples 1-3 performed significantly better in the fatigue life test, especially Example 3, whose fatigue life reached 1,900,000 cycles, which was significantly better than the comparative sample. This shows that the composite modified material and the two-step heat treatment have a significant effect on improving the anti-fatigue performance.

[0104] Comparative Example 1 has the shortest fatigue life (950,000 times), and no trace elements and nanoparticles are added, resulting in poor fatigue resistance. Comparative Examples 2-5 have some improvements, but are still lower than the examples.

[0105] IV. Conclusion

[0106] The following conclusions can be drawn from the analysis of the experimental results of Examples 1-3 and Comparative Examples 1-5:

[0107] 1. Material modification and heat treatment significantly improve the tensile strength, ductility and wear resistance of the material, especially Example 3, through the addition of composite trace elements and nanoparticles, and double-step heat treatment, the material performance is optimally improved.

[0108] 2. The double-step heat treatment is effective in optimizing internal stress and dimensional stability. The residual stress and dimensional deviation of the embodiment are small, while the dimensional stability and fatigue resistance of the materials of comparative examples 4 and 5, which were not subjected to double-step heat treatment, are significantly reduced.

[0109] 3. The segmented multi-step cold heading and local heating technology improves the fatigue resistance, improves the forming accuracy, and enhances the reliability of the studs under high stress and complex working conditions.

[0110] In summary, the cold heading forming process of the present invention significantly improves the strength, ductility, wear resistance, dimensional stability and fatigue resistance of the copper alloy studs through material modification and process optimization, and is suitable for the manufacture of high-performance components for new energy DC motor guides.

Claims

1. A cold heading forming process for copper alloy double-headed studs guided by new energy DC motors, characterized in that: The process includes the following steps: 1) Material pretreatment: Choose aluminum bronze CuAl 10 Fe3Mn2 is used as a matrix material, and trace elements of yttrium, lanthanum, magnesium, titanium, zirconium and boron are added to the matrix material, and the contents of the trace elements are: yttrium and lanthanum are 0.01-0.15%, magnesium is 0.2-0.5%, titanium and zirconium are 0.01-0.05%, and boron is 0.01-0.03%; and nano-tungsten carbide and nano-alumina particles are added to the material, and the addition amount of the nano-particles is 0.01-0.1%; 2) Two-step heat treatment: The modified copper alloy is heated to 700-750℃ and kept at this temperature for 1-2 hours, followed by rapid cooling to obtain a material with refined grains; then low-temperature tempering is performed at 250-300℃ for 1-2 hours to evenly distribute trace elements, eliminate internal stress, and improve material ductility and fatigue resistance; 3) Segmented multi-step cold heading: The material is subjected to segmented multi-step forming on the cold heading machine.

2. The cold heading forming process according to claim 1, characterized in that: The amount of yttrium added is 0.005%-0.1%, and the amount of lanthanum added is 0.005%-0.1%.

3. The cold heading forming process according to claim 1, characterized in that: The addition amount of titanium is 0.005-0.04%, and the addition amount of zirconium is 0.005-0.03%.

4. The cold heading forming process according to claim 1, characterized in that: The addition amount of nano tungsten carbide is 0.005-0.08% and the addition amount of nano alumina particles is 0.005-0.05%.

5. The cold heading forming process according to any one of claims 1 to 4, characterized in that: The segmented multi-step cold heading forming step includes the following sub-steps: a) Preforming: Use a cold heading machine to preliminarily shape the copper alloy billet to obtain the basic shape of the stud; b) Local heating fine forming: The thread and end structure of the stud are heated by induction heating to increase the local temperature to 200-250℃ to increase ductility and improve forming accuracy; c) Final forming: Further fine forming is performed to obtain the final stud structure to ensure its dimensional accuracy and strength.

6. The cold heading forming process according to claim 5, characterized in that: The heating temperature in the local heating fine forming step is 200-250° C., and the heating time is 1-2 seconds.

7. The cold heading forming process according to claim 5, characterized in that: The punching pressure in the preforming stage of the segmented multi-step cold heading forming step is 15-20 tons, the punching pressure in the fine forming stage is 20-25 tons, and the punching pressure in the final forming stage is 25-30 tons.

8. The cold heading forming process according to claim 5, characterized in that: The surface of the mold used in the segmented multi-step cold heading forming step has a nano-composite coating, and the coating is a TiN / CrN nano-multilayer composite coating or a boron nitride (BN) self-lubricating coating.

9. The cold heading forming process according to claim 5, characterized in that: After cold heading, the stud is rapidly isothermally cooled to room temperature.

10. A copper alloy stud obtained by the cold heading forming process according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Copper-based composite material and preparation method thereof

    CN112210688A

  • Flange plate bolt and manufacturing method and using method thereof

    CN114233736A